Optimization of explant sterilization mode for Juglans regia L. - Ryzhenko, T. S. (Forestry and Forest Melioration, 2021)
Introduction Breeding of Persian walnut (Juglans regia L.) by the individual selection method was started in Ukraine in the 1930s (Skorobogatyj, 1936; Yermolenko, 1935, 1936). In vitro propagation of walnuts has played a very important role in the rapid spread of the desired varieties and the production of healthy disease-free plants. The biggest challenge in walnut micropropagation is the explant sensitivity to oxidation by phenolic compounds. A considerable number of studies have been made to address this problem. Less problematic are infectious diseases of explants, rooting, and difficulties associated with the transplanting to the soil (humidity, temperature, natural light). For the walnut, it is important to conduct experiments to improve micropropagation methods due to economic and environmental significance for the further spread of genetically homogeneous material. The aim of the study was to determine the most effective methods for sterilization of plant material of Juglans regia L. Materials and Methods The study was conducted in the laboratory of microclonal propagation in URIFFM. Due to the shortage of juvenile grafted material, we used plant material selected in Kharkiv, from one plant from January through April, although it is known that juvenile nut tissues are more favourable for in vitro culture. For sterilization of explants from pathogenic microflora, three variants of the chemical composition with various periods of sterilizer action were used. A total of three experiments were set up (11 variants). Experiment 1. The plant material was washed with a brush under running water with the addition of detergent (Fairy). Explants in the form of micro-cuttings with one (rarely two) buds were washed in a soap solution for 20 minutes. After washing, the explants were sterilized with a 70% ethanol solution (0.5–3 minutes) followed by washing in sterile distilled water. The next stage of sterilization was immersion in a 1% silver nitrate (AgNO3) solution (0.5–4 minutes) followed by rinsing in sterile distilled water. Then the explants were treated with a 30% hydrogen peroxide (H2O2) solution for 3 minutes. After sterilization, the explants were washed with sterile distilled water three times for 3 minutes and planted on MS medium without modification. Experiment 2. The material was washed with a brush under running water with the addition of detergent (Fairy). Explants in the form of micro-cuttings with one (sometimes two) buds were washed in a soap solution for 20 minutes. After washing, the explants were sterilized with a 70% ethanol solution (30 sec–3 minutes) followed by washing in sterile distilled water. Then they were immersed in a 10% solution of Lysoformin-3000 (5–15 minutes). After sterilization, the plants were washed with sterile water for 10 minutes and planted on MS medium without modification. Experiment 3. The material was treated with detergents before sterilization. All steps were repeated from Experiment 1. MS medium with the addition of the Cefotaxime antibiotic (400 mg/l) was prepared and then poured it into sterile Petri dishes. We placed 3–5 explants in the Petri dishes and placed them in the refrigerator for 1–2 days. Then the explants were transplanted to MS medium without modifications. For seven days, the sterilization efficiency was determined in each of the variants by determining the number of sterile and infected explants. The viability of the introduced explants was assessed after 25 days by determining the proportion of sterile and infected explants. Results Using AgNO3 as one of the main components of sterilizing substances with a short exposure time (0.5–1 minutes), we received 97% and 76% of infected explants and 3– 12% of necrotized ones. Prolonged exposure to sterilizing substances – 2 minutes in ethanol solutions and more than 1 minute in silver nitrate solution (AgNO3) – led to tissue necrotization in most explants. In the experiment, 12–14% of morphologically active regenerants were obtained; however, if ethanol exposure time increased up to 2 minutes, the proportion of morphologically active walnut plants decreased. This indicates the low efficiency of these chemicals in such a combination. When using Lysoformin-3000 10% as a sterilizing substance, we failed to obtain viable explants due to necrotization (3–37%) and infection with fungi and bacteria (63–100%). Therefore, such a sterilization procedure is ineffective. When using AgNO3 with the addition of Cefotaxime in the nutrient medium (400 mg/l), the percentage of infected explants decreased from 100–45 to 39–9%. In this case, we received 65–73% of morphologically active explants. The addition of the antibiotic to the medium increased the yield of sterile walnut explants. This sterilization mode helps to overcome phenolic intoxication and inhibit the development of internal infections. One of the problems of walnut reproduction in vitro is the inhibition of the growth of morphologically active plants after antibiotic sterilization. Optimization of the sterilization regime and microclonal propagation of the best forms of walnut are subjects of further research. Conclusions The use of Lysoformin-3000 as a sterilizing agent was not effective. Silver nitrate (AgNO3) did not help to fight the internal infection with a subsequent necrotization of the walnut micro shoots. Regarding the use of the Cefotaxime antibiotic in the nutrient medium (MS without modifications), it showed a positive result in fighting phenolic intoxication and infection in Persian walnut explants.